The impact of the financial crisis on transatlantic information flows: An intraday analysis - Thomas Dimpfl; Franziska J. Peter (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
We use intraday stock index return data from both sides of the Atlantic during overlapping trading hours to analyze the dynamic interactions between European and US stock markets. We are particularly interested in differences of information transmission before, during, and after the financial crisis of 2007 to 2009. Our analysis draws on the concept of Rényi transfer entropy to allow for a flexible and model-free empirical assessment of linear as well as non-linear market dependencies. Thereby the importance of extreme (tail) observations of the return distributions is highlighted. The results show significant bi-directional information transfer between the US and the European markets with a dominant flow from the US market. During the crisis dynamic interactions increase. At the same time information flows from European markets increase. The US market does not entirely regain its leading role in the after crisis period.
urn:nbn:de:bsz:21-opus-72334
Keywords: C58; G14; G15; 330; stock market indices; information flows; financial crisis; Rényi transfer entropy; transatlantic information transmission